Genetic influences in gastro-oesophageal reflux disease: a twin study. Issue 8 (15th July 2003) - Mohammed, I; Cherkas, L F; Riley, S A; Spector, T D; Trudgill, N J
Abstract : Background: A number of families have been described which include multiple members with symptomatic, endoscopic, or complicated gastro-oesophageal reflux disease (GORD). First degree relatives of patients with GORD are more likely to suffer with GORD symptoms. These observations raise the possibility of a genetic contribution to the aetiology of GORD. Aims: To determine the relative contribution of genetic factors to GORD by evaluating GORD symptoms in monozygotic (MZ) and dizygotic (DZ) twins. Methods: A total of 4480 unselected twin pairs, identified from a national volunteer twin register, were asked to complete a validated symptom questionnaire. GORD was defined as symptoms of heartburn or acid regurgitation at least weekly during the past year. Results: Replies were obtained from 5032 subjects (56% response rate). A total of 1960 twin pairs were evaluable: 928 MZ pairs (86 male pairs, mean (SD) age 52 (13) (range 19–81) years) and 1032 DZ pairs (71 male pairs, mean age 52 (13) (20–82) years). The prevalence of GORD among both groups of twins was 18%. Casewise concordance rates were significantly higher for MZ than DZ twins (42% v 26%; p<0.001). Multifactorial liability threshold modelling suggests that additive genetic effects combined with unique environmental factors provide the best model for GORD. Heritability estimates suggest that 43% (95% confidence interval 32–55%) of the variance in liability to GORD is due to additive genetic factors. Conclusions: There is a substantial genetic contribution to the aetiology of GORD.